Communicating values through the Madrasah - Elequin, Eleanor T. (Education quarterly.)
The Madrasah is to be viewed in a perspective: as an instrument of uplifting the economic, social and cultural condition of Muslim communities; as an instrument for attaining national solidarity at the same time, that is to be strengthened as an intitution for instilling in the Muslim children the necessary consciousness that as Muslim they are part and parcel of the unity of the world Islamic Um'mah.